Financial Feasibility Study Of Laying Chicken Farming Business In Pure 2 Hall, Sinyonyoi Village, Kalukku District - Fadhill, Muhammad; Mariam, Mariam; Kaharuddin, Kaharuddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the financial feasibility of a laying hen farm in Pure 2 Hamlet, Sinyonyoi Village, Kalukku District, Mamuju Regency, using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) indicators, with income varying each semester. The Payback Period (PP) is 4.24 months, the Net Present Value (NPV) is positive at Rp 1,137,000,233, and the Internal Rate of Return (IRR) is very high (140.7% per semester or 479.4% per year). These results indicate that the Awing Laying Hen Farm is financially viable and has great potential for success